A Multi-Layered Framework for Analyzing Primary Students' Multimodal Reasoning in Science - Lihua Xu; Jan van Driel; Ryan Healy (MDPI AG, 2021)
Classroom communication is increasingly accepted as multimodal, through the orchestrated use of different semiotic modes, resources, and systems. There is growing interest in examining the meaning-making potential of other modes (e.g., gestural, visual, kinesthetic) beyond the semiotic mode of language, in classroom communication and in student reasoning in science. In this paper, we explore the use of a multi-layered analytical framework in an investigation of student reasoning during an open inquiry into the physical phenomenon of dissolving in a primary classroom. The 24 students, who worked in pairs, were video recorded in a facility purposefully designed to capture their verbal and non-verbal interactions during the science session. By employing a multi-layered analytical framework, we were able to identify the interplays between the different semiotic modes and the level of reasoning undertaken by the students as they worked through the tasks. This analytical process uncovered a variety of ways in which the students negotiated ideas and coordinated semiotic resources in their exploration of dissolving. This paper highlights the affordances and challenges of this multi-layered analytical framework for identifying the dynamic inter-relationships between different modes that the students drew on to grapple with the complexity of the physical phenomenon of dissolving.